2017
DOI: 10.1159/000479088
|View full text |Cite
|
Sign up to set email alerts
|

Trigonelline Inhibits Inflammation and Protects β Cells to Prevent Fetal Growth Restriction during Pregnancy in a Mouse Model of Diabetes

Abstract: Background: As an active component from traditional Chinese medicine, trigonelline has a protective effect on diabetes. This study evaluated the protective effects of trigonelline on diabetic mice during pregnancy. Methods: Diabetes was induced in female mice by intraperitoneal injection for continuous 5-day of 40 mg/kg/day streptozotocin. Female mice were divided into 4 groups after they were allowed to mate with normal male mice: nondiabetic, nondiabetic treated with trigonelline (70 mg/kg) for 18 days, diab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 36 publications
1
13
0
Order By: Relevance
“…Different plant parts contain active compounds that act at multiple targets in the inflammatory response pathways and regulate a multitude of chemical mediators, enzymes, genes or cellular functions to alleviate inflammation [30] and hence, outcomes of assays that utilize extracts are expected to reflect a net effect of such potential multitarget interactions that may also apply to M. subcordata extracts. The PPARγ agonists' ability to inhibit inflammatory responses by repressing NF-κB target genes has been linked to the prevention and treatment of the metabolic syndrome and diabetes [77,78]. Likewise, the induction of PPARγ mediated gene expression as well as inhibition of NO production by M. subcordata extracts and candidate constituents thereof may imply that M. subcordata may have potential anti-inflammatory effects possibly by inhibiting NF-κB signalling pathways although the data in the present study are not enough to claim anti-inflammatory effects and that further studies are required.…”
Section: Discussionmentioning
confidence: 99%
“…Different plant parts contain active compounds that act at multiple targets in the inflammatory response pathways and regulate a multitude of chemical mediators, enzymes, genes or cellular functions to alleviate inflammation [30] and hence, outcomes of assays that utilize extracts are expected to reflect a net effect of such potential multitarget interactions that may also apply to M. subcordata extracts. The PPARγ agonists' ability to inhibit inflammatory responses by repressing NF-κB target genes has been linked to the prevention and treatment of the metabolic syndrome and diabetes [77,78]. Likewise, the induction of PPARγ mediated gene expression as well as inhibition of NO production by M. subcordata extracts and candidate constituents thereof may imply that M. subcordata may have potential anti-inflammatory effects possibly by inhibiting NF-κB signalling pathways although the data in the present study are not enough to claim anti-inflammatory effects and that further studies are required.…”
Section: Discussionmentioning
confidence: 99%
“…Noteworthily, trigonelline was first identified in Lycium fruits, and its content distribution in different Lycium species also was conducted and varied. Several previous studies have been focused on the protective effects of trigonelline on testicular tissue injury induced by heat stress in mice, or the treatment of nephrotic syndrome [23–25]. Trigonelline must be further investigated to determine whether it acts as a new quality and bioactive marker responsible for its pharmacological activities and quality assessments of Lycium fruits.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that TRG exists in many plant species such as Allium sepapea, Pissum sativum, Glycine max, Zea mays, Hordeum vulgare, Lycopersicon esculentum, and Coffea spp. There is evidence that TRG possessed different pharmacological effects like hypoglycemic, hypolipidemic, neuroprotective, antimigraine, sedative, memory-improving, antibacterial, antiviral, and anti-tumor activities [21][22][23][24]. The present study was designed to investigate the antidepressant-and anxiolytic-like effects of TRG in a mouse model of MS stress focusing on oxidative stress parameters including NO, MDA, and antioxidant capacity.…”
Section: Introductionmentioning
confidence: 99%